Professionalism of Project Management Team and Implementation of National Government Constituency Development Funded Projects in Kenya - Amayo Meshack Otieno; Jackline Akoth Odero; Ben Oseno (Journal of Business and Social Review in Emerging Economies)
Purpose: The study examined influence of Professionalism of Project Management Team on the Implementation of National Government-Constituency Development Funded Projects in Kenya.